Enhancing parental well-being and coping through a family-centred short course for Iranian parents of children with an autism spectrum disorder. (January 2013) - Samadi, Sayyed Ali; McConkey, Roy; Kelly, Greg
Parents of children with Autism Spectrum Disorders (ASD) generally experience high levels of stress and report poorer emotional well-being and family functioning compared to parents of children with other disabilities. They also tend to rely on emotional rather than problem-focused coping strategies. Seven group-based sessions were offered to two groups of parents of children with ASD in Iran (37 in all). In addition to providing information about ASD emphasis was placed on families sharing their experiences and learning from one another. A pre-post, cross-over design was used to evaluate the specific impact of the course. The changes found among the parents in the first group were replicated with the second group. Moreover the changes were sustained up to 15 weeks after the course ended. Although there were variations across the parents, in general they reported feeling less stress, had better emotional wellbeing and family functioning and made more use of problem-focused coping strategies. The changes were attributed mainly to an increase in the informal supports among the parents and their feelings of empowerment. A resource pack has been developed to enable the group sessions to be easily repeated and for facilitators to be trained in its use.